2012
DOI: 10.1136/neurintsurg-2012-010523
|View full text |Cite
|
Sign up to set email alerts
|

Transfemoral endovascular treatment of atherosclerotic stenotic lesions of the left common carotid artery ostium: case series and review of the literature

Abstract: In our experience, transfemoral stenting of stenotic LCCAO lesions is feasible and no permanent neurological or cardiopulmonary sequelae occurred in 14 patients treated with this technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 17 publications
1
11
0
Order By: Relevance
“…Surgical treatment of CCA ostial lesions has been performed with bypass surgery (subclaviancarotid, carotid-carotid), although this procedure requires thoracotomy or median sternotomy and carries a perioperative mortality of approximately 6% [12]. Thus, endovascular approaches have become increasingly preferable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Surgical treatment of CCA ostial lesions has been performed with bypass surgery (subclaviancarotid, carotid-carotid), although this procedure requires thoracotomy or median sternotomy and carries a perioperative mortality of approximately 6% [12]. Thus, endovascular approaches have become increasingly preferable.…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports on stenting of the CCA ostium employ techniques similar to those used in our first case [3,12]. In brief, a diagnostic catheter is used to select the involved CCA, carefully traversing the ostial lesion.…”
Section: Discussionmentioning
confidence: 99%
“…To the present, techniques including the coaxial use of a distal protection device and a 0.014-inch guidewire, 10) penetration of the stenosed area using a guiding catheter, 11) and the use of two distal balloon protection devices 12) have been reported. From the viewpoint of prevention of distal embolism as a complication, passing the guiding catheter through the stenosed area should be avoided.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9][10][11][12] While reports restricting the target to the common carotid artery lesions are few, Linni et al 9) observed the absence of cranial nerve damage and lymphorrhea as advantages of endovascular treatment in a study restricted to 52 patients with common carotid artery lesions and recommended endovascular treatment as the first choice and other direct surgical procedures as useful alternatives. Van de Weijer et al 18) reported that lesion cross was impossible in 4 of the 144 patients who underwent endovascular treatment, particularly, in 2 of the 5 patients with occluded lesions.…”
Section: Disclosure Statementmentioning
confidence: 99%
See 1 more Smart Citation